جماليات الامر و النهي في القران الكريم : سورة البقرة انمودجا - سهير باي, امال قديري (My University, 2019)
ملخص: تعد البلاغة العربية من أكثر علوم اللغة العربية أهمية، لأنها سبيل لمعرفة كتاب الله وإبراز أسراره البيانية، وهذه الدراسة لمعرفة دلالات الأمر والنهي المختلفة في سورة البقرة،الذي ترتب عليه كثير من الأحكام والمعاملات المتعلقة بها في استنباط الأحكام الشرعية للأمر والنهي في هذه الصورة، اتبعت في هذه الدراسة المنهج الوصفي وتوصلت إلى أن الأمر والنهي ورد كثيرا في سورة البقرة، وكان الأمر أكثر ورودا من النهي، وورد الأمر بصيغه المختلفة، غير أن صيغة الأمر الصريح الأكثر ورودا من خلال الدراسة وهذا ما يوحي إلى حتمية الأمر ووجوبه، وأقلها صيغة اسم فعل الأمر، إن للأمر والنهي دلالات تفهم من صيغ الألفاظ وقرائن الأحوال، وتختلف هذه الدلالات باختلاف أراء المفسرين والعلماء باختلاف القراءات القرآنية، ويعد كل من الأمر والنهي صيغا دالة على معرفة الأحكام الشرعية من الحلال والحرام والإباحة وغيرها، ورد الأمر في سورة البقرة في مائة وعشرين آية وورد النهي في أربع وخمسين آية. Abstract Arabic eloquence is one of the most significant sciences of Arabic language. And because it is the way of knowing the Holy Quran revels his clearest secret, this study has aimed of knowing the difference evidences of the prohibition and commanding in SoraElbagara in which is arranged plenty of rules and treatment that are related to it, significantly in minority and majority of theformulation of the inhibition and commanding in this Sora. And this study has been followed by descriptive analytical . And this study has reached that the prohibition and commanding is mentioned very much is SoraElbagara and commanding was mentioned much more than of the imperative less. The commanding and the expression formulas. These evidences can be different according the views of the scenarists and explainers in the difference of the Holy Quran readings. Each of the commanding and prohibit considered formula indicates to know the legal rules of permitting forbidding and so the prohibition has been generally remained in 54 verses. key words: eloquence, prohibition, commanding, evidence, formulation, descriptive analytical
Keywords: الكلمات المفتاحية: البلاغة، النهي، الأمر، الدلالة، الصيغ، التحليل الوصفي.